2014
DOI: 10.1039/c3dt52989d
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic study on the formation of Cm(iii) acetate complexes at elevated temperatures

Abstract: The complexation of Cm(III) with acetate is studied by time resolved laser fluorescence spectroscopy (TRLFS) as a function of ionic strength, ligand concentration, temperature and background electrolyte (NaClO4, NaCl and CaCl2 solution). The speciation of Cm(III) is determined by peak deconvolution of the emission spectra. To obtain the thermodynamic stability constants (log K) for the formation of [Cm(Ac)n](3-n) (n = 1-3), the experimental data are extrapolated to zero ionic strength according to the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
6
16
3
Order By: Relevance
“…The solution phase speciation for Cm 3+ in dilute buffered solutions (0.1 M) was in agreement with previous studies suggesting that the Cm 3+ -aquo ion existed in dilute acetate solutions. 9 Data herein is also comparable with previous reports on the Cm 3+ -aquo ion. For instance, the coordination numbers and bond-distances that we obtained were consistent with single crystal data from Cm(H 2 O) 9 3+ , 39,40 which showed six H 2 O ligands with short Cm–O H2 O distances [2.453(1) Å] and three H 2 O ligands with longer Cm–O H2 O distances, 2.545(1) Å.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The solution phase speciation for Cm 3+ in dilute buffered solutions (0.1 M) was in agreement with previous studies suggesting that the Cm 3+ -aquo ion existed in dilute acetate solutions. 9 Data herein is also comparable with previous reports on the Cm 3+ -aquo ion. For instance, the coordination numbers and bond-distances that we obtained were consistent with single crystal data from Cm(H 2 O) 9 3+ , 39,40 which showed six H 2 O ligands with short Cm–O H2 O distances [2.453(1) Å] and three H 2 O ligands with longer Cm–O H2 O distances, 2.545(1) Å.…”
Section: Resultssupporting
confidence: 92%
“…One of many examples includes actinides dissolved in buffered ammonium acetate and acetic acid solutions, (NH 4 )O 2 CMe (aq) :HO 2 CMe (aq) . Beyond a few focused studies, [2][3][4][5][6][7][8][9] this stock solution is poorly characterized because of the inherent challenges associated with handling highly radioactive actinides. Interpreting spectroscopic results from actinides in this complicated aqueous environment is also challenging in comparison to well-dened organic solutions as well as when frozen in the solid-state.…”
Section: Introductionmentioning
confidence: 99%
“…As the charge neutralization model is based on the assumption that one Eu(III) or Cm(III) ion occupies three proton exchange sites of the FA molecule the presently determined thermodynamic constants are compared to literature values of 1 : 3 complexes of Cm(III) and Eu(III) with simple organic ligands (acetate, 50 salicylate 51 ) at I = 0.1 M. In the case of acetate, stability constants at I = 0.1 M are calculated from the stability constants at zero ionic strength reported in ref. 50 using the specific ion interaction theory. Then, Δ r H m and Δ r S m at I = 0.1 M are determined using the Van't Hoff equation.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that apparent complex formation constants between radionuclides and LMWO tend to increase with temperature. 12 Various groundwater compositions are observed depending on the disposal site considered. For instance, OPA exhibits pore waters with ionic strengths between I = 0.3-0.5 M (e.g.…”
Section: Introductionmentioning
confidence: 99%